Investing for a Greener, Competitive and Socially Inclusive Europe - Debora Revoltella; Patricia Wruuck (Vierteljahrshefte zur Wirtschaftsforschung, 2020)
Development banks are there for good times as well as bad times. They promote structural changes in economies, addressing longer-term challenges. They complement financial systems, helping to improve the functioning of banking and financial markets and bolstering economic resilience. They mitigate market failure, but can also help to identify it, contributing to the design of effective policy. Moreover, development banks can help to create and shape markets, such as the green bonds market. In doing so, they catalyse structural economic transformation and spur investment-led growth. For the post-Covid-19 world, Europe needs structural trans- formation to address the challenges of rapid technological change and stiffer global competition, growing threats to social cohesion and, not least, climate change. In this article, with a focus on the role of the EIB, we discuss three main questions: What is the rationale for development banks? What is the EIB's unique position within the European development banking landscape? And how is the EIB helping to address the key challenges that Europe is currently facing, boosting recovery from the historic Covid-19 shock to create a more competitive, inclusive and greener economy in Europe? – – Förderbanken sind in guten und in schlechten Zeiten nützlich. Sie bringen strukturelle Veränderungen in Volkswirtschaften voran und helfen dabei, langfristige Herausforderungen anzugehen. Sie ergänzen Finanzsysteme, unterstützen die Funktionsfähigkeit von Banken- und Finanzmärkten und stärken die Resilienz von Volkswirtschaften. Sie lindern nicht nur Marktversagen, sondern können aber auch einen Beitrag dazu leisten, diese zu identifizieren und so durch Politikmaßnahmen effektiv zu adressieren. Darüber hinaus können Förderbanken helfen, Märkte zu schaffen und zu formen, wie etwa für grüne Anleihen. Auf diese Weise wirken sie als Katalysator für wirtschaftliche Transformationsprozesse und kurbeln Wachstum getrieben durch Investitionen an. Für die Welt, die der Covid-19 Pandemie folgt, braucht Europa strukturelle Veränderungen, um die Herausforderungen durch schnellen technologischen Wandel, verschärften globalen Wettbewerb, wachsende soziale Ungleichheit und nicht zuletzt den Klimawandel erfolgreich anzugehen. In diesem Beitrag, der auf die Rolle der EIB eingeht, diskutieren wir drei Kernfragen: Warum gibt es Förderbanken? Welche besondere Position nimmt die EIB im System der europäischen Förderbanken ein? Wie trägt die EIB dazu bei, die gegenwärtig wesentliche Herausforderung einer schnellen wirtschaftlichen Erholung Europas nach dem historischen Covid-19 Schock zu unterstützen und dabei gleichzeitig eine wettbewerbsfähigere, sozial gerechtere und grünere Wirtschaft zu schaffen?
Keywords: G20; O10; O16; O38; L52; P16; 330; Competition; Covid-19; development bank; digitalisation; EIB; green bond; infrastructure; social inclusion; structural transformation